Hubungan TBC Dan Pertumbuhan Anak : Edukasi Nakes Kader Ibu Balita di Prambon - Nurmaya, Ika; Soeyono, Rahayu Dewi; Dewi, Ratna Candra; Sholakhuddin, Ahmad; Manik, Dina Mariana (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
The total number of Tuberculosis cases in Prambon sub-district is 140 cases, Treatment Coverage (Tc-%) reaches 59.32%, and Tuberculosis Cases in Children 0-14 Years are 30 Children. The large number of TB children who have risk factors for growth retardation requires the role of health workers, cadres, and mothers of toddlers in recognizing TB symptoms and supporting the intake of nutritional intake. The aim of this activity is to increase the knowledge of health workers, cadres, and mothers of toddlers regarding childhood TB and its relationship to stunting through online education.  Initial activities were carried out by assessing participants' knowledge about Recognizing Childhood TB and its relationship to stunting through administering a pre-test before the educational session, followed by the delivery of instructional materials, and concluding with a post-test. The results of education for 41 participants showed that participants' knowledge increased by an average knowledge score of 8,97% after education. The results of educational activities recognizing childhood TB and its relationship to stunting. There was positive feedback and strong communication between the participants and presenters. Education on recognizing childhood TB led to a notable increase in participant knowledge and its relationship to stunting for participants.Keywords: children with Tuberculosis; nutritional intake; nutritional counseling; stunting. Abstrak: Jumlah kasus Tuberkulosis di Kecamatan Prambon sebanyak 140 kasus, Cakupan Pengobatan (Tc-%) mencapai 59,32%, dan Kasus Tuberkulosis pada Anak Usia 0-14 Tahun sebanyak 30 Anak. Banyaknya anak TB yang memiliki faktor risiko retardasi pertumbuhan memerlukan peran serta tenaga kesehatan, kader, dan ibu balita dalam mengenali gejala TB dan mendukung pemenuhan asupan gizi. Tujuan kegiatan ini adalah meningkatkan pengetahuan tenaga kesehatan, kader, dan ibu balita mengenai TBC anak dan kaitannya dengan stunting melalui edukasi daring. Untuk mengukur tingkat pemahaman peserta mengenai TBC dan Asupan gizi seimbang dalam rangka pencegahan stunting, diadakan kegiatan edukasi daring melalui Zoom Meeting dengan metode presentasi menggunakan PowerPoint. Kegiatan awal dilakukan pre-test sebelum edukasi, kemudian pemberian materi dan dilanjutkan post-test. Hasil Edukasi terhadap 41 peserta menunjukkan bahwa pengetahuan peserta mengalami peningkatan  pada rata-rata skor pengetahuan sebesar 8,97% setelah edukasi. Hasil kegiatan edukasi mengenali TBC anak dan hubungannya dengan stunting menunjukkan respon yang positif dan komunikasi yang baik dari peserta dengan pemateri. Kesimpulannya adalah terjadi peningkatan pengetahuan peserta setelah diberikan edukasi Mengenali TBC anak, dan hubungannya dengan Stunting bagi peserta.Kata kunci: anak yang Tuberkulosis; asupan gizi; penyuluhan gizi; stunting